Ultralight, Strong and Renewable Hybrid Carbon Nanotubes Film for Oil-Water Emulsions Separation - Yamei Lu; Yingze Cao; Yi Jia; Chunai Dai; Pengfei Wang (Membranes, 2020)
A novel ultralight superhydrophobic-superoleophilic hybrid Carbon Nanotubes (CNTs) film with double-layer structures is fabricated by using vacuum filtration method. The CNTs film can separate various surfactant-stabilized water-in-oil emulsions with a separation efficiency higher than 99.3%. Moreover, the hybrid films can be regenerated through a simple and rapid combustion process within 2 s. In addition, the CNTs film still retains good hydrophobic properties under the conditions of physical abrasion, and strong acidic and alkaline solutions, which shows the excellent durability. The hybrid CNTs film is ultralight, stable, and easily stored and reused. The outstanding features of the obtained CNTs films we present here may find many important applications in various fields like oil purification and wastewater treatment.